Grow wider canopies or thicker stems: Variable response of woody plants to increasing dryness. Issue 1 (13th November 2020) - Ding, Jingyi; Travers, Samantha K.; Eldridge, David J.
Abstract: Aim: Woody plants vary greatly from tall trees to branching shrubs with increasing dryness. Variation in plant allometry is driven by both biotic and abiotic factors, reflecting different plant adaptation strategies in different environments. Here, we explore how aboveground allometry of different woody plants responds to increasing dryness along an extensive aridity gradient. Location: Eastern Australia. Time period: 2018–2019. Major taxa studied: Woody plants. Methods: We surveyed the aboveground allometry of woody plants (e.g., canopy, height, stem diameter, branches) at 150 sites along a 1, 500‐km aridity gradient from humid to arid areas. We used regression analyses and structural equation modelling to explore the variation in woody allometry with increasing aridity, and the abiotic (resource availability) and biotic (aboveground competition) mechanisms driving such changes. Results: Plant height declined, but branching, canopy width and canopy depth increased with increasing aridity. Woody responses to dryness varied among genera, with increasing aridity associated with wider canopies in Eucalyptus and Callitris spp., thicker stems in Acacia spp., but no clear differences in Allocasuarina spp. Biotic and abiotic factors exerted different effects on the allometry of different genera, with Eucalyptus and Callitris spp. constrained by resource availability, while Acacia and Allocasuarina spp. were regulated mainly by aboveground competition. Main conclusions: As aridity increased, we found genus‐specific responses in allometric changes and driving mechanisms (resource availability cf. aboveground competition). Rather than merely shrinking in size, our results suggest that woody plants allocate resources to either canopies or stems to cope with increasing dryness. Increasing stem or canopy size, and altering branching might be a useful strategy for woody plants to compensate for biomass reduction and maintain functions while growing shorter under hotter and drier climates.